Tardive intermittent massive vaginal bleeding from abnormal blood vessels within cesarean scar: Two more new cases should bring our attention to a new entity. Issue 6 (8th March 2016) - Liao, Xiangling; Zhang, Pu; Zhang, Caiyi; Lu, Gary
Abstract: The two cases in this report had intermittent massive vaginal bleeding with a distant history of cesarean delivery. Such severe bleeding was life‐threating but was eventually cured by surgical management. To the best of our knowledge, this is the second report of cases of tardive vaginal bleeding caused by abnormal blood vessels embedded within cesarean scars. The two new cases in this report suggest a novel cause of tardive vaginal bleeding, which should bring our special attention to post‐cesarean clinical practice.